The positive economics of labor market rigidities and investor protection - Rainer Fehn; Carsten-Patrick Meier (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper presents a positive model which shows that institutional setups on capital and labor markets might be intertwined by politicoeconomic forces. Some countries especially in continental Europe exhibit a corporatist politicoeconomic equilibrium with a sustantial protection of insiders on both markets. The more important money is in political decision-making, the more devided the workface is, and the more globalized capital markets are, the more likely is a capitalist politicoeconomic equilibrium with little employment and substantial investor protection. Our prediction of a negative cross-country relationship between labor market rigidities and of competition on capital markets receives considerable empicical support.
Keywords: G34; K22; K42; 330; labor markets; employment protection; corporatism; corporate governance; shareholder protection; political economy; Arbeitsmarktflexibilisierung; Korporatismus; Public Choice; Arbeitsrecht; Aktienrecht; Corporate Governance; Insider-Outsider-Modell; Schätzung; Theorie; Welt